2020
DOI: 10.1186/s13568-020-01086-4
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a recombinant chickenized monoclonal antibody against the neuraminidase of H9N2 avian influenza virus

Abstract: We previously reported a monoclonal antibody (mAb), 1G8, against the neuraminidase (NA) of H9N2 avian influenza virus (AIV) with significant NA inhibitory activity. To generate a recombinant chickenized mAb (RCmAb) against the NA of H9N2 AIV for passive immunization in poultry, the gene of the fragment of antigen binding (Fab) of mAb 1G8 was cloned and fused with the fragment crystallizable (Fc) gene of chicken IgY. The RCmAb 1G8 was expressed in COS-1 cells and could be detected in cell culture supernatant. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…We previously reported a mAb 1G8 against NA of H9N2 AIV, which possesses NI activity ( Wan et al, 2016 ; Wang et al, 2020 ). We now further identified that mAb 1G8 cannot only cross-react with NAs of H9N2 AIV and H3N2 HSIV but also have NI activity to them in NI assays.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a mAb 1G8 against NA of H9N2 AIV, which possesses NI activity ( Wan et al, 2016 ; Wang et al, 2020 ). We now further identified that mAb 1G8 cannot only cross-react with NAs of H9N2 AIV and H3N2 HSIV but also have NI activity to them in NI assays.…”
Section: Discussionmentioning
confidence: 99%
“…However, components in raw sera have anti-NA properties that result in inhibition of NA activity. The ELLA is used to measure antibody-mediated NA inhibition for cleaving a large substrate, and has been used to assess the effectiveness of NA-containing vaccines and anti-NA antibodies (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Allantoic fluid of each virus was harvested at 120 h post-inoculation and stored at −70°C. The pCAGGS plasmid, containing NA gene sequence of a wild-type (WT) A/Chicken/Jiangsu/XXM/1999 (XXM) H9N2 virus, was constructed, as previously reported [ 23 ].…”
Section: Methodsmentioning
confidence: 99%